2011
DOI: 10.1111/j.1365-313x.2010.04439.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome landscape of Arabidopsis male meiocytes from high‐throughput sequencing: the complexity and evolution of the meiotic process

Abstract: SUMMARYMeiosis is essential for eukaryotic sexual reproduction, with two consecutive rounds of nuclear divisions, allowing production of haploid gametes. Information regarding the meiotic transcriptome should provide valuable clues about global expression patterns and detailed gene activities. Here we used RNA sequencing to explore the transcriptome of a single plant cell type, the Arabidopsis male meiocyte, detecting the expression of approximately 20 000 genes. Transcription of introns of >400 genes was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
183
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(201 citation statements)
references
References 98 publications
(210 reference statements)
18
183
0
Order By: Relevance
“…This idea is supported by the observations that simultaneous silencing of both genes results in a dwarf phenotype but that mutations in either gene alone do not cause developmental abnormalities (Kevei et al, 2011). In addition, CDC20.1 is expressed at high levels in male meiocytes (Yang et al, 2011), but CDC20.2 expression is nearly undetectable, suggesting that CDC20.1 might have a more prominent role than CDC20.2 in meiosis.…”
Section: Cdc201 Is Required For Male Fertility In Arabidopsissupporting
confidence: 70%
“…This idea is supported by the observations that simultaneous silencing of both genes results in a dwarf phenotype but that mutations in either gene alone do not cause developmental abnormalities (Kevei et al, 2011). In addition, CDC20.1 is expressed at high levels in male meiocytes (Yang et al, 2011), but CDC20.2 expression is nearly undetectable, suggesting that CDC20.1 might have a more prominent role than CDC20.2 in meiosis.…”
Section: Cdc201 Is Required For Male Fertility In Arabidopsissupporting
confidence: 70%
“…Studies in yeast, flies, and humans showed that the POL2 N terminus is important for elongation and fidelity of DNA replication (19,21), whereas the C-terminal region is essential for cell viability. Arabidopsis has two POL2 homologs (POL2A and POL2B), and POL2A was expressed in male meiocytes, whereas POL2B was almost undetectable (22), suggesting a potential function of POL2A in meiosis. To test this hypothesis, we obtained three pol2a mutants (SI Appendix, Fig.…”
Section: Pol2amentioning
confidence: 99%
“…Transcriptomic studies have been conducted in pollen, sperm, and anthers in diverse plant species, including Arabidopsis, rice, B. rapa, maize, and cotton (Gossypium hirsutum; Honys and Twell, 2004;Ma et al, 2007Ma et al, , 2008Ma et al, , 2012Chen et al, 2010;Fujita et al, 2010;Deveshwar et al, 2011;Yang et al, 2011;Dong et al, 2013;Wuest et al, 2013). While some studies were focused on tapetum and male gametophytes, others compared anthers of male sterile mutants with anthers of the wild type.…”
Section: Anthers Of Floral Stage 9 Transiently Express a Large Numbermentioning
confidence: 99%